Interpolation of nonlinear functionals by integral continued fractions - Mykhal'chuk, B. R. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We constructively prove the theorem of existence of an interpolation integral chain fraction for a nonlinear functionalF:Q[0,1]→R 1.